Clinical Presentation and Outcomes of Patients With a Lumbar Far Lateral Herniated Nucleus Pulposus as Compared to Those With a Central or Paracentral Herniation. Issue 5 (August 2019) - Khan, Jannat M.; McKinney, Dennis; Basques, Bryce A.; Louie, Philip K.; Carroll, Deven; Paul, Justin; Varthi, Arya; Iyer, Sravisht; An, Howard S.
Study Design: Retrospective cohort study. Objectives: Examine pre- and postoperative outcomes between patients presenting with a central/paracentral versus a far lateral herniated nucleus pulposus (HNP) and assess whether significantly worse postoperative outcomes, assessed via patient self-reported survey, are associated with far lateral disc herniations. Methods: We performed a retrospective cohort analysis of patients who underwent primary lumbar decompression between January 2008 and December 2015. Groups were divided based on herniation type, central/paracentral or far lateral. Patients with 3 months, or longer, of follow-up were included. Variables analyzed included demographics, American Society of Anesthesiologists (ASA) Score, Charleston Comorbidity Index (CCI), Oswestry Disability Index (ODI) scores, Visual Analog Scales (VAS) scores for the back and leg, 12-Item Short Form Mental and Physical Survey (SF-12) scores, and Veterans RAND 12-Item Mental and Physical Survey (VR-12) scores. Results: A total of 100 patients met the inclusion criteria. Postoperative ODI scores for central/paracentral HNP were significantly lower compared to far lateral HNP. Patients with a far lateral disc herniation presented with significantly lower preoperative SF-12 and VR-12 scores. The improvement in ODI score from preoperative to final was significantly lower in the patients presenting with a far lateral HNP. Conclusions: Although patients with far lateral HNP present with worse preoperative outcome scores, they can expect similar symptom improvement to central or paracentral herniations following discectomy. This information can be used for future surgeons when weighing conservative versus surgical treatment of far lateral herniations.